Exploring terrestrial lightning parameterisations for exoplanets and brown dwarfs. (15th September 2021) - Hodosán, G.; Helling, Ch.; Vorgul, I.
Abstract: Observations and models suggest that the conditions to develop lightning may be present in cloud-forming extrasolar planetary and brown dwarf atmospheres. Whether lightning on these objects is similar to or very different from what is known from the Solar System awaits answering as lightning from extrasolar objects has not been detected yet. We explore terrestrial lightning parameterisations to compare the energy radiated and the total radio power emitted from lightning discharges for Earth, Jupiter, Saturn, extrasolar giant gas planets and brown dwarfs. We find that lightning on hot, giant gas planets and brown dwarfs may have energies of the order of 10 11 –10 17 ​J, which is two to eight orders of magnitude larger than the average total energy of Earth lightning (10 9 ​J), and up to five orders of magnitude more energetic than lightning on Jupiter or Saturn (10 12 ​J), affirming the stark difference between these atmospheres. Lightning on exoplanets and brown dwarfs may be more energetic and release more radio power than what has been observed from the Solar System. Such energies would increase the probability of detecting lightning-related radio emission from an extrasolar body. Highlights: Experience from the Solar System suggests that lightning exists in exoplanetary and brown dwarf atmospheres. Exo-lightning power will be strongly dependent on the metallicity and surface gravity of the object. Exo-lightning may be two-eight orders of magnitude more energetic than Earth lightning. Exo-lightning energies may be up to five orders of magnitude larger than lightning on Jupiter or Saturn. Such energies make future detections of exo-lightning conducted over multiple wavelengths probable.